MODAL SOSIAL TIM PENGGERAK PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (TP PKK) KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Anggiet Anika Putri; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Family empowerment and welfare (PKK) is the gesture of the communitydevelopment grows from under, its management from, by, and for community.PKK is one of by society movement who are active in Enok District and theirmembers the majority are woman. The community supports PKK Enok Districtbecause it aims to improve the quality of human resources related to theempowerment of society which will affect the welfare of life, especially the familywelfare. The formulation of the problem discussed in this research is socialcapital in the Family Empowerment and Welfare Team (TP PKK) Enok Districtand efforts to maintain and Family Empowerment and Welfare Team (TP PKK)Enok District. The subjects of this research are 6 people where the subject of thisresearch are active members in the Enok District Family Empowerment andWelfare Team (TP PKK). The technique of determining informant in this researchis by using purposive sampling technique. The method used is descriptivequalitative research method. The theory used is social capital theory put forwardby Putnam consisting of social network, norms social, and trust. The result of thestudy it can be concluded that social capital that it is extremely important in anorganization, social capital what is most evident on the team the driving force ofthe Family Empowerment and Welfare (TP PKK) Enok District promised tosupply the social networks and the weak thing that on the norms social. Tomaintain and raise capital social in the coordinator of Family Empowerment andWelfare (TP PKK) Enok District namely by maintain social networks andincrease norms social in the coordinator of Family Empowerment and Welfare(TP PKK) Enok District.Keywords: Family Empowermant and Welfare, Social Capital